Exhaust Emissions and Physicochemical Properties of Hydrotreated Used Cooking Oils in Blends with Diesel Fuel - Iraklis Zahos-Siagos; Dimitrios Karonis (International Journal of Chemical Engineering, 2018)
Hydroprocessing of liquid biomass is a promising technology for the production of “second generation” renewable fuels to be used in transportation. Its products, normal paraffins, can be further hydrotreated for isomerization in order to improve their cold flow properties. The final product, usually referred to as “paraffinic diesel,” is a high cetane number, clean burning biofuel which is rapidly gaining popularity among researchers and the industry. Nevertheless, the costly isomerization step can be omitted if normal paraffins are to be directly mixed with conventional diesel in low concentrations. In this work, nonisomerized paraffinic diesel produced through hydrotreating of used cooking oil (hydrotreated used cooking oil (HUCO)) has been used in 4 blends (up to 40% v/v) with conventional diesel fuel. The blends’ properties have been assessed comparatively to European EN 590 and EN 15940 standards (concerning conventional automotive diesel fuels and paraffinic diesel fuels from synthesis or hydrotreatment, resp.). Furthermore, the HUCO blends have been used in a standard stationary diesel engine-generator set. The blends have been considered as “drop-in replacements” for standard diesel fuel. As such, no engine modifications took place whatsoever. The engine performance and exhaust emissions of steady-state operation have been examined in comparison with engine operation with the baseline conventional diesel fuel.